2006
DOI: 10.1158/1535-7163.mct-06-0170
|View full text |Cite
|
Sign up to set email alerts
|

A novel plant toxin, persin, within vivoactivity in the mammary gland, induces Bim-dependent apoptosis in human breast cancer cells

Abstract: Phytochemicals have provided an abundant and effective source of therapeutics for the treatment of cancer. Here we describe the characterization of a novel plant toxin, persin, with in vivo activity in the mammary gland and a p53-, estrogen receptor -, and Bcl-2-independent mode of action. Persin was previously identified from avocado leaves as the toxic principle responsible for mammary gland -specific necrosis and apoptosis in lactating livestock. Here we used a lactating mouse model to confirm that persin h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 23 publications
2
55
0
Order By: Relevance
“…MCF-7 cells stably overexpressing human BCL-2 have been previously described (Butt et al, 2006). 4-OHT was purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…MCF-7 cells stably overexpressing human BCL-2 have been previously described (Butt et al, 2006). 4-OHT was purchased from Sigma-Aldrich (St Louis, MO, USA).…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Chemotherapeutic properties of plant chemicals, or phytochemicals, have been studied and some found to have antitumor activity, providing effective therapeutic treatment. According to Butt et al (2006), the most widely used phytochemicals are taxanes, such as paclitaxel and its derivatives, which are effective against some types of breast, ovary, and other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Persin is a phytochemical that has been isolated from the avocado plant (Persea americana); persin is synthesized in the plant's idioblast oil cells from long-chain fatty acids, presumably as an insecticide and fungicide (Butt et al, 2006;Rodriguez-Saona and Trumble, 2000). It was previously shown that ingestion of avocado leaves by lactating livestock causes mastitis and decreased milk production, associated with necrosis of the secretory epithelium of mammary glands, as well as interstitial edema, congestion and hemorrhage (Kingsbury, 1964, pp.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations